2012
DOI: 10.4103/0189-6725.99412
|View full text |Cite
|
Sign up to set email alerts
|

Colostomy in neonates under local anaesthesia: Indications, technique and outcome

Abstract: Colostomy in neonates under local anaesthesia is feasible, safe and cost-effective. The outcome is good and may be used when neonatal anaesthetic expertise and intensive care facilities are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…A divided distal descending/sigmoid colostomy is increasingly being performed for fecal diversion in the management of patients with ARM (6769). An historical comparison of the management of children with ARM over two decades in Zaria, Nigeria showed that 69 patients who required a colostomy in the first 10 years (January 1988 to December 1997) of the review had transverse loop colostomy compared to 96 patients in the latter 10 years (January 1998 to December 2007) who had divided sigmoid colostomy (13).…”
Section: Surgical and Perioperative Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…A divided distal descending/sigmoid colostomy is increasingly being performed for fecal diversion in the management of patients with ARM (6769). An historical comparison of the management of children with ARM over two decades in Zaria, Nigeria showed that 69 patients who required a colostomy in the first 10 years (January 1988 to December 1997) of the review had transverse loop colostomy compared to 96 patients in the latter 10 years (January 1998 to December 2007) who had divided sigmoid colostomy (13).…”
Section: Surgical and Perioperative Considerationsmentioning
confidence: 99%
“…Colostomy for ARM may be associated with complications in 12.9–78.9% (Table 2) of African children (14, 18, 68, 69, 74). The most commonly reported complications following colostomy for ARM are prolapse, skin excoriations and hemorrhage (Table 2).…”
Section: Surgical and Perioperative Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present described laparoscopic procedure, as with all other surgical interventions, may also lead to minor complications such as skin infection and discomfort during management of the colostomy bag after surgery. [7][8][9] Severe wound infection, stoma prolapse, and evisceration can also occur.…”
Section: Discussionmentioning
confidence: 99%